2003
DOI: 10.1136/jnnp.74.7.946
|View full text |Cite
|
Sign up to set email alerts
|

Interferon beta in multiple sclerosis: experience in a British specialist multiple sclerosis centre

Abstract: Background: The efficacy of interferon beta (IFN beta) is well established in relapsing-remitting multiple sclerosis (MS). However, the use of this drug in clinical practice is complex, especially because it is only partially effective, its long term efficacy and side effects are unknown, its efficacy may be abrogated by the development of neutralising antibodies, compliance is variable, and its cost effectiveness is controversial. Objectives and Methods: Analysis of a prospectively followed up series of 101 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 14 publications
4
24
0
1
Order By: Relevance
“…These results were similar to those given in other published series [15, 19]. The reduced annualized relapse rate (0.78 in the pivotal trial versus our 0.7) in our series was similar to previously reported figures [2, 15, 19, 20]. …”
Section: Discussionsupporting
confidence: 82%
“…These results were similar to those given in other published series [15, 19]. The reduced annualized relapse rate (0.78 in the pivotal trial versus our 0.7) in our series was similar to previously reported figures [2, 15, 19, 20]. …”
Section: Discussionsupporting
confidence: 82%
“…Beta-interferon (IFN-β), an approved treatment for MS, is an antiviral and an immunomodulatory cytokine that may modify the clinical course of the disease, specially in relapsing-remitting MS (RRMS) patients with acute demyelinating events [1, 2, 3, 4]in the following way: reduction in the 3-year cumulative probability of developing clinically definite MS, significant reduction of new T2 lesions, gadolinium-enhanced lesions and T2 lesion volume, reduction of tissue damage and promotion of lesion recovery in RRMS patients, and effective in reducing the relapse rate in patients with RRMS in routine clinical practice, i.e. change from baseline in mean number of exacerbations and proportion of exacerbation-free patients; however, we do not completely know what immunomodulatory mechanisms may be involved in the mediation of its positive effects in the treatment of MS patients, although it has been suggested that its antiviral properties contribute to its efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…A 24hr protein collection quantitated proteinuria at 21.54 gm/24hr and creatinine clearance of 94 ml/min. Urinalysis showed 30 WBCs/cm 3 , 20 RBCs and no casts. Urine protein electrophoresis showed unselective protein loss.…”
Section: Case Reportmentioning
confidence: 99%
“…2,3 Three preparations are available. Interferon β1b is distributed as Betaseron in North America and Betaferon in Europe and the Middle East.…”
mentioning
confidence: 99%